Design of Multimedia College in Banda Aceh with Modern Architecture Approach - Ayuni Namira (Universitas Syiah Kuala, 2019)
Education and information and communication technology continue to develop along with the progress of the times to produce quality human resources. This should be supported by educational facilities that can facilitate the public in their knowledge in the field of information and communication technology (multimedia). College of Multimedia are colleges that hold special education programs in the multimedia field. Therefore, this writing aims to create or design a college of multimedia that can accommodate the activities of its users. This design takes the theme of Modern Architecture. Multimedia College is closely related to technology that will continue to keep abreast of the times. Judging from the function of the building which is a multimedia college, it must show modern buildings that follow the current technology.